Self-regulated learning of prospective mathematics teachers with different learning styles - Aryo Andri Nugroho; Dwi Juniati; Tatag Yuli Eko Siswono (Universitas Islam Negeri (UIN) Mataram, 2020)
[English]: Self-regulated learning and learning styles are two of the various factors which contribute to students' achievement in learning at each level of education, including mathematics teacher education. This study examined the self-regulated learning of prospective mathematics teachers (PMT) with different learning styles (visual, auditory, kinesthetic). It involved 66 PMTs who enrolled on a linear program course in the 4th semester. Data were collected through a questionnaire, a test, and a semi-structured interview. The test was used to select PMTs who have high mathematics ability as the subjects. They were provided with the questionnaire to examine their fulfilment of cognition, motivation, behaviour, and context in the four stages of self-regulated learning. The interview was administered to confirm and thoroughly explore subjects' responses in the questionnaire. The results of the questionnaire and interview were qualitatively analyzed. This study found that PMT with different learning styles fulfils four aspects of self-regulated learning in the stage of (1) planning, forethought, and activation, (2) monitoring, (3) control, and (4) reaction and reflection in different extent, preference, and strategies. The differences are possibly affected by their different learning styles. Keywords: Self-regulated learning, Learning styles, Prospective mathematics teachers [Bahasa]: Kemandirian belajar dan gaya belajar merupakan dua dari banyak faktor yang mempengaruhi capaian siswa dalam pembelajaran di setiap level pendidikan termasuk pendidikan guru matematika. Penelitian ini bertujuan menganalis kemandirian belajar mahasiswa calon guru matematika yang memiliki gaya belajar berbeda (visual, audio dan kinestetik). Penelitian melibatkan 66 mahasiswa pendidikan matematika semester 4 yang sedang mengambil kuliah program linier. Pengumpulan data dilakukan dengan tes kemampuan matematika, angket kemandirian belajar, dan wawancara semi struktur. Tes digunakan untuk memilih calon guru yang memiliki kemampuan matematika tinggi sebagai subjek. Subjek terpilih diberikan angket untuk mengetahui tingkat capaian kognisi, motivasi, perilaku dan konteks dalam empat tahap kemandirian belajar. Wawancara dilakukan untuk mengonfirmasi dan memperdalam pilihan subjek pada angket. Data hasil angket dan wawancara dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa calon guru matematika dengan gaya belajar berbeda memenuhi empat aspek kemandirian belajar pada tahap (1) perencanaan, pemikiran, dan aktivasi, (2) pengawasan, (3) kontrol, dan (4) reaksi dan refleksi dalam tingkatan, pilihan, dan strategi yang berbeda. Perbedaan tersebut kemungkinan dipengaruhi oleh kecenderungan gaya belajar yang dimiliki calon guru. Kata kunci: Kemandirian belajar, Gaya belajar, Calon guru matematika